Pengembangan Penyandian Dalam Aplikasi Pada Kriptografi Dengan Menggunakan Metode RC6 Berbasis Web - Rinaldy Chaniago; Jonson Manurung (Pustaka Timur Publisher, 2021)
Cryptography is the art of encoding to keep messages from being easy to read, or commonly called secret messages. There are two main concepts, namely encryption, and decryption. Encryption is the process by which the information sent is converted into a form that is not recognized as the initial information by using a certain algorithm. Decryption is the opposite of encryption which is changing back the disguised form into initial information. In data encoding, namely document encoding with the RC6 method, it is carried out to secure the document into a file that cannot be read by others so that the data can be said to be safe, the data will be changed in content and format so that only those who have the key can return the data into data. readable start. In the design in building the document data security encoding application, supporting applications are used, namely sublime text and the xampp database so that the application built is web-based.